Tingkat Stres Akademik pada Mahasiswa Keperawatan Tahun Pertama (Journal of Telenursing (JOTING), 2025)
This study aims to determine the factors that cause academic stress in first-year nursing students. The method used is quantitative descriptive. The results showed that most students experienced high levels of academic stress, with an average score of 101.85 which is included in the category of severe stress. As many as 60% of respondents were in the category of severe or very severe stress. The most dominant questionnaire items showed that physiological symptoms such as fatigue and excessive sweating were common indications of stress experienced. In conclusion, the most dominant factors causing academic stress in first-year nursing students were physiological symptoms such as fatigue and excessive sweating.Keywords: Nursing Students, Academic Stress Level.